Nox2 Regulates Platelet Activation and NET Formation in the Lung - Hook, Jessica S.; Cao, Mou; Potera, Renee M.; Alsmadi, Nesreen Z.; Schmidtke, David W.; Moreland, Jessica G. (Frontiers in Immunology, 2019)
The mortality rate of patients with critical illness has decreased significantly over the past 2 decades, but the rate of decline has slowed recently, with organ dysfunction as a major driver of morbidity and mortality. Among patients with the systemic inflammatory response syndrome (SIRS), acute lung injury is a common component with serious morbidity. Previous studies in our laboratory using a murine model of SIRS demonstrated a key role for NADPH oxidase 2 (Nox2)-derived reactive oxygen species in the resolution of inflammation. Nox2-deficient (gp91phox-/y) mice develop profound lung injury secondary to SIRS and fail to resolve inflammation. Alveolar macrophages from gp91phox-/y mice express greater levels of chemotactic and pro-inflammatory factors at baseline providing evidence that Nox2 in alveolar macrophages is critical for homeostasis. Based on the lung pathology with increased thrombosis in gp91phox-/y mice, and the known role of platelets in the inflammatory process, we hypothesized that Nox2 represses platelet activation. In the mouse model, we found that platelet-derived chemokine (C-X-C motif) ligand 4 (CXCL4) and CXCL7 were increased in the bronchoalveolar fluid of gp91phox-/y mice at baseline and 24 hours post intraperitoneal zymosan-induced SIRS consistent with platelet activation. Activated platelets interact with leukocytes via P-selectin glycoprotein ligand 1 (PSGL-1). Within 2 hours of SIRS induction, alveolar neutrophil PSGL-1 expression was higher in gp91phox-/y mice. Platelet-neutrophil interactions were decreased in the peripheral blood of gp91phox-/y mice consistent with movement of activated platelets to the lung of mice lacking Nox2. Based on the severe lung pathology and the role of platelets in the formation of neutrophil extracellular traps (NETs), we evaluated NET production. In contrast to previous studies demonstrating Nox2-dependent NET formation, staining of lung sections from mice 24 hours post zymosan injection revealed a large number of citrullinated histone 3 (H3CIT) and myeloperoxidase positive cells consistent with NET formation in gp91phox-/y mice that was virtually absent in WT mice. In addition, H3CIT protein expression and PAD4 activity were higher in the lung of gp91phox-/y mice post SIRS induction. These results suggest that Nox2 plays a critical role in maintaining homeostasis by regulating platelet activation and NET formation in the lung.